THE MICROBIOLOGICAL QUALITY OF SOME RAW MILK PRODUCTS - Rasha M.Othman; Nawras N.Japer; Alaa T. Abdul Alwahid (Basrah Journal of Veterinary Research)
Seventy five white cheese, semi-white cheese and cream (25 samples of each )were randomly collected from different area in basrah city and were investigated for microbiological quality.In these samples, the numbers of microorganisms were found as follows:14.13x104 cfu/g ,16.46x103 cfu/g and 12.36x103 cfu/g for total mesophilic bacteria , 9.87 X102 cfu/g total Psychrotrophic bacteria of cream , 12.92 X103 cfu/g, 6.97X102 cfu/g and 6.13 X102 cfu/g staphylococcus aureus, 98.72 X103 cfu/g,10.55 X102 cfu/g and 6.54 X102 cfu/g coliform count , 21.77 X102 cfu/g , 6.47 X102 cfu/g and 6.40 X102 cfu/g Escherichia coli .Total Psychrotrophic bacteria were not detected in white cheese and semi-white cheese . Significant (p<0.05) variations were found between raw white cheese, semi-white cheese and cream whereas no Significant variations were found between semi-white cheese and cream for all microbial group. The microbiological findings showed the presence of high counts of microorganisms investigated and the poor hygienic quality